(3MGTjI Ydi eNJUQ JdNjU GdeaJGM ddJaJGRGfjs - (3GdSeQbfOj, efdG RGOg, CMeO Hf YKeGf, J(B901(3g`s ((3YHO Gddg Hf HTjQ GdHhSfhjs)
(3ChdgG (B:s
(3fMeOc Gddge Ydi eG CYWjJfG ef ShGHZ GdfYe hHhGdZ GdMcefMeOc CKQ GMeO Ydi GdTcQ dCf GdMeO jYe GdaVGFd hGdahGVds
(3BNQgG (B:s
(3hGdChdi Cf jbGHd GdeJQhc HGdeJQhc Edjg ajbGd jJQc GdeYjf Edi ZjQ GdeYjf Ch GdNWGH eY GdeYjf Edi GdNWGH eY ZjQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: 1 / 192s
(3cTa GdXfhf(B: 1 / 476s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs